Beskrivelse uden sted:: Om Giorgio Agambens paradigmeteori og det litterært singulære - Andersen, Jørn Erslev (Slagmark - Tidsskrift for idéhistorie, 2015)
The essay presents Giorgio Agamben’s theory of the paradigm in the first chapter of The Signature of All Things. On Method (2009) in order to better understand the well-known use of references to and qoutations from literature (poems and novels) in philosophical reasoning and theory. Agamben’s uncommented reference to two short stanzas from Wallace Stevens’ poem “Description without Place”, which he consider the best definition of a paradigmatic ontology, is briefly commented. A gathering of three ‘literary singularities’ from Friedrich Hölderlin/Sophocles, James Joyce, and Samuel Beckett in a suggested paradigm on time is presented as an example of a solely literary way of philosophical thinking.